1983
DOI: 10.1128/iai.40.2.825-828.1983
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of common treponemal antigens

Abstract: A molecular characterization of cross-reactive antigens of Treponema pallidum Nichols and Treponema phagedenis biotype Reiter that are reactive with normal and syphilitic human sera is described. At least 8 common polypeptides, 14 T. pallidum-specific antigens, and 2 T. phagedenis biotype Reiter-specific antigens were identified.Antigenic characterization of Treponema pallidum has been hampered by the inability to obtain large quantities of pure, motile, and virulent organisms (1,9,10,21,22,(28)(29)(30). Nonpa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
11
1

Year Published

1984
1984
2013
2013

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 23 publications
5
11
1
Order By: Relevance
“…Utilizing sera from syphilitic patients and the Western blotting technique, Hanff et al (5) recently characterized eight protein antigens with MW of 30,000, 33,000, 35,500, 40,000, 45,000, 47,000, 73,000, and 82,000 that are common to both T. pallidum and T. phagedenis biotype Reiter. Using a crossed immunoelectrophoresis technique, Pedersen et al (10) have identified six cross-reacting protein antigens.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Utilizing sera from syphilitic patients and the Western blotting technique, Hanff et al (5) recently characterized eight protein antigens with MW of 30,000, 33,000, 35,500, 40,000, 45,000, 47,000, 73,000, and 82,000 that are common to both T. pallidum and T. phagedenis biotype Reiter. Using a crossed immunoelectrophoresis technique, Pedersen et al (10) have identified six cross-reacting protein antigens.…”
Section: Discussionmentioning
confidence: 99%
“…Lukehart et al (7), using sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) followed by Western blotting (11), have identified at least eight antigens of T. pallidum which react with a serum pool from infected rabbits. By the same technique, Hanff et al (4,5) have studied the humoral immune response to protein antigens of T. pallidum in human syphilis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The nonpathogenic, cultivatable treponemes provide an alternative means for the study of analagous T. pallidum constituents at the molecular level. It has been demonstrated by Western blotting (13,20) and crossed immunoelectrophoresis (27)(28)(29) that nonpathogenic treponemes, specifically Treponema phagedenis biotype Reiter, possess a number of polypeptides that are cross-reactive with proteins of T. pallidum. Antisera raised to these purified, cross-reactive proteins can be used as probes for characterization and ultrastructural localization of the corresponding molecules in T. pallidum.…”
mentioning
confidence: 99%
“…Basic questions about the composition of the Treponema pallidum cell surface and the biological functions of its component molecules have been difficult to answer because in vitro multiplication of the organism is limited (6) and growth in rabbit testicles creates the inherent problem of interpreting whether molecules copurified with T. pallidum are rabbit or treponemal in origin. Recent approaches to define T. pallidum antigens have utilized immunoprecipitation of T. pallidum polypeptides radiolabeled in vitro (2, 12a, 14, 17) or immunoblotting of T. pallidum polypeptides with syphilitic sera (7,8,10,17). More than 20 antigens have been identified in human and experimental syphilis.…”
mentioning
confidence: 99%